Antibody responses induced by the BNT162b2 mRNA COVID-19 vaccine in healthcare workers in a single community hospital in Japan. Issue 4 (April 2022) - Otsuka, Shinya; Hiraoka, Kei; Suzuoki, Masato; Ujiie, Hideki; Kato, Tatsuya; Yokota, Isao; Yonezawa, Kazuya; Oguma, Keiji; Iwashiro, Nozomu; Kato, Mototsugu; Ohara, Masanori
Abstract: Introduction: The effectiveness of several vaccines against coronavirus disease (COVID-19) has been reported in the real-world setting. However, it is still unknown how long antibodies persist following vaccination and whether or not the persistence of antibodies has a protective effect against COVID-19. Methods: Healthcare workers who had received two doses of the BNT162b2 mRNA COVID-19 vaccine were enrolled, and a single-center study was conducted at the National Hospital Organization Hakodate National Hospital. Serum samples from all participants were collected 13–21 weeks (median: 20 weeks) after the second dose of vaccination. The antibody titers were measured using an electrochemiluminescence immunoassay (Elecsys® Anti-SARS-CoV-2 S). Data on characteristics of the participants were gathered from patient records and interview sheets. Results: A total of 401 participants, among whom 70.1% were women and the median age was 42 years, were evaluated in this study. None of the participants had a definite COVID-19 history, and all participants who received complete vaccination showed positive antibody titers. The antibody titer was observed to be higher in participants with younger age (p < 0.001) and those who were females (p = 0.028). Despite the higher risk of infection than that of the general public, no vaccinated staff developed breakthrough infections. Conclusions: This study demonstrates the significant contribution of the BNT162b2 vaccine in the acquisition of anti-SARS-CoV-2S antibodies; therefore, the general population should benefit from these two vaccine doses, which are expected to be protective for at least five months.